National research on the postgraduate student experience : case presentation : volume 1 : first year postgraduate student experience. - Kinash, Shelley; Crane, Linda; Bannatyne, Amy; Judd, Madelaine-Marie; Stark, Ashley; Eckersley, Bill; Hamlin, Gary; Partridge, Helen; Udas, Ken (Office of Learning and Teaching, 2016)
This is volume one of a set of case studies that explore the postgraduate student experience. The theme of this case study is first year postgraduate student experience and is based on experiences derived from student engagement breakfasts, interviews, and focus groups with 366 people across the stakeholder groups of postgraduate students, educators, and university executives from 26 institutions. The case studies constitute part of the output from the project, Engaging postgraduate students and supporting higher education to enhance the 21st century student experience.